2015
DOI: 10.4103/0972-0707.153069
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation of mineral trioxide aggregate (MTA) to root dentin surface with orthograde/retrograde application techniques: A microcomputed tomographic analysis

Abstract: Background:Achieving a good apical seal for root canals is known to be associated with good mineral trioxide aggregate (MTA) adaptation to dentin.Aims:This study aims to compare the marginal adaptation of MTA with root dentin between orthograde and retrograde application techniques using microcomputed tomography (micro-CT) analysis.Settings and Design:Fifty-two single-rooted human teeth were divided into four equal groups: (Group 1) Retrograde MTA (RMTA), (Group 2) Orthograde MTA (OMTA), (Group 3) Etched RMTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Considering the marginal adaptation of MTA to root dentin, a recent study[ 37 ] using microcomputed tomographic analysis has shown that the type of application technique (either orthograde or retrograde) do not significantly improve the dentin-MTA adaptation, instead with the use of 17% EDTA, a significant improvement could be achieved. In this study, a significant difference in the gap volumes was observed between retrograde MTA (RMTA filling without etching) and etched RMTA (ERMTA) (etching before retrograde filling) where etching significantly improved the MTA-dentin adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the marginal adaptation of MTA to root dentin, a recent study[ 37 ] using microcomputed tomographic analysis has shown that the type of application technique (either orthograde or retrograde) do not significantly improve the dentin-MTA adaptation, instead with the use of 17% EDTA, a significant improvement could be achieved. In this study, a significant difference in the gap volumes was observed between retrograde MTA (RMTA filling without etching) and etched RMTA (ERMTA) (etching before retrograde filling) where etching significantly improved the MTA-dentin adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Commendable is the fact that almost half of the respondents use MTA for retrograde filling. MTA is believed to be a bioactive material with several favorable properties, such as stimulating cementum and hard tissue formation, and having an antibacterial effect due to its alkaline pH (10.2-12.5) (1,3,15). Newly introduced materials (Biodentine, Bioaggregate, iRoot BP Plus) have also shown comparable biocompatibility with a potential to provide favorable environment for the cell, showing cell proliferation and osteogenic capability but further research and clinical trials are required (16,17,18,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…22 açık apeksli dişlerin başarı oranlarını rapor ettikleri tarihsel kohort çalışma sonuçlarına dayanarak, açık apeksli dişler için en uygun tedavi seçeneği olarak apikal tıkaç oluşturmak için MTA'nın ortognatik yolla gönderilmesini önermektedirler. Al Fouzan ve arkadaşlarının 23 MTA'nın dentine adaptasyonunun değerlendirdikleri bir çalışmada, MTA'nın ortograd veya retrograd uygulamaları arasında istatistiksel olarak fark olmadığı sonucuna varmışlardır. Sunulan bu çalışmada, MTA'nın retrograd veya ortograd uygulamasının simüle immatür dişlerin kırılma dayanımına etkisinin incelenmesi amaçlanmıştır.…”
Section: Discussionunclassified